Estudo in vivo da impedância do canal radicular dentário em função da frequência - Rambo, Marcos Vinicio Haas (2012)
Electronic foramen locators are becoming more popular in the endodontic therapy for the determination of the working length. The working length delimits the deepest point in the root canal that instruments may reach during root canal treatment, and its accurate determination is a key factor for the success of endodontic therapy. The radiographic method is traditionally used in this surgical step, but electronic methods have proved to be faster, more precise and safer. Several electronic methods have been proposed and studies assessing the accuracy of these devices were published. The evaluation of the impedance between the two test probes used by the electronic devices, the endodontic file and the hook shape electrode that is attached to the oral mucosa membrane, has also been the subject of several studies. However, there is a lack of in vivo evaluations of the root canal impedance in the literature. The present work tries to fulfill this gap with in vivo investigative studies of the root canal impedance. The results of these studies were used to model the frequency response of the root canal impedance and to find equivalent circuits that represent the inclination of the frequency response in logarithmic scale. They were also employed in the development of an innovative electronic foramen locator based on the spectral attenuation coefficient of the root canal impedance. With the prototype used in the in vivo characterization of the root canal impedance, another study was conducted to assess the ratio method, which is one of the electronic techniques used to locate the apical foramen.